Analysis of the Textbook Ayo Belajar Bahasa Arab according to Jean Piaget’s Cognitive Development Theory - Jaziela Huwaida; Alin Safaraz Himam; Siti Anne Barkah Nur Fauziah; Abdul Hafidz binZaid; Cecep Sobar Rochmat (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This study aimed to determine the quality of textbook content Ayo Belajar Bahasa Arab in terms of the cognitive aspects of Jean Piaget’s Cognitive Development Theory. This research is a qualitative analytical study by library research methodology. The main data sources are the textbooks of Ayo Belajar Bahasa Arab and lots of the latest studies. The analysis was done by analyzing the content of relevant data using the cognitive development qualifications of Jean Piaget. The results of this study are concluded that the purpose of the textbooks studied is in accordance with the abilities of children aged 11 or grade 5 elementary school according to Jean Piaget's theory of cognitive development. Matching one thing with another, understanding conversations, discussing and arguing with the guidance of the teacher, and classifying sentences from Arabic to Indonesian are the abilities students need to study the textbook according to their goals. Appropriate book material is learning vocabulary, practicing conversation, reading, and constructing sentences and exercises. The analysis results show that Ayo Belajar Bahasa Arab’s book achieves excellent results on the suitability and appropriateness to the theory of cognitive development of Jean Piaget.